Blockchain technology development and business applications - Jain, Akshit Kumar (Nanyang Technological University, 2024)
This paper presents a blockchain-based property auction marketplace attempting to revolutionize traditional real estate transactions by eliminating the need for intermediaries known as property brokers. Leveraging blockchain technology, the marketplace offers transparency, security, and efficiency and addresses existing challenges in the real estate industry. Smart contracts ensure trustless execution of property auctions, eliminating the need for intermediaries and enhancing transactional integrity. The marketplace's decentralized nature fosters a level playing field for landlords and renters, promoting inclusivity and accessibility in property transactions. Overall, the blockchain-based property auction marketplace represents a paradigm shift towards a more transparent, efficient, and accessible real estate ecosystem.